PENGARUH MOTIVASI KERJA, KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN X - Magfiroh 5130019029, Wan Azizatul (Economics and Business Faculty UNUSIA, 2022)
Human resources are the most important factor in a company's ability to carry out its business activities, so it is imperative that companies have a pool of qualified employees. Investing in high-quality human resources is both a short-term and long-term strategy for a company or organization. If the company wants high-quality and professional human resources, it must continually develop each employee's skills and reward them accordingly. This article's goal is to examine the link between employee performance and work motivation and satisfaction. This study's methodology is based on a review of existing literature. Reading announcements, summaries, letters, and other written materials is an auxiliary method for collecting data. The findings of this study show that employee performance is positively impacted by work motivation. Employee productivity is positively correlated with job satisfaction. In addition, job satisfaction and work motivation have a positive and significant impact on employee performance. Keywords: Work motivation, job satisfaction, employee performance